FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENCEGAHAN JATUH PADA PASIEN RISIKO JATUH OLEH PERAWAT DI RUANG NUSA INDAH RSUD TUGUREJO SEMARANG - Marina Nugraheni; Baju Widjasena; Bina Kurniawan; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The incident of falling patient in hospital are three major medical incidents that may cause minor injuries to death if there is notany prevention. The beginning of research results indicated that most accident cases in RSUD Tugurejo Semarang was patient falls cases and in the last two years there was incidence of patients falling in Nusa Indah. This research aimed to analyzed the related factors associated with falling patient prevention by nurses Nusa Indah RSUD Tugurejo. This research is a Descriptive correlation with cross sectional approach. The population of this research consist of nurses who on duty in Nusa Indah Room 2, 3, and 4. The sample of this research used a total sampling,those sum of all nurses nurses who on duty in Nusa Indah Room, totally 40 nurses. Based on the analysist of data obtained using Rank Spearman Test, related variables to the fall prevention of falling risk patient were the knowledge of nurse (p-value 0,02), training (p-value 0,035), and supervision (p-value 0,008). While unrelated variables to the fall prevention of falling risk patient were age (p-value 0,863), tenure (p-value 0,680), and condition of infrastructur (p-value 0,495). The researcher suggest to hospitals for prevention of falling patient are reform the content of policies and guidelines related to the use of patient falls yellow bracelet into yellow label at the door of the patient, create a Standard Operasional Prosedur about prevention of falling patient more specifically, the establishment of the monitoring patient safety team of RSUD Tugurejo Semarang in each room that played an active role in providing optimal monitoring implementation of prevention patient falls and put up the yellow sign should match with risk fall guidelines’s sheets of RSUD Tugurejo Semarang.